1988
DOI: 10.1136/oem.45.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Forestry workers exposed to vibration: a neurological study.

Abstract: Neurological findings were examined in 186 forestry workers with a mean exposure to chain saw vibration of 16-6 hours. The prevalence of active vibration induced white fingers was 5%, parethaesias of the hands 53%, and muscle weakness 13%. Clinical polyneuropathy was observed in 16 forestry workers in the hands (7.5%) which did not correlate with alcohol consumption. Seventy nine forestry workers of the total population were selected for electromyographic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 8 publications
4
23
0
Order By: Relevance
“…The concurrence between current exposures and sensorineural symptoms in 2001, compared with 1988, may indicate a more temporal or episodic pattern of disease. It is consistent with the observation by Farkkila et al [1988] that, among forest workers, reduced tool vibration had less of an effect on neurological symptoms than vascular symptoms, because of the persistence of biomechanically influenced disorders, such as CTS. Self-reported prior physician diagnosis of CTS had a monotonic association with current exposure, and increased to over 35% of workers in the highest exposure group in the 2001 survey.…”
Section: Effects Of Exposure Reductionsupporting
confidence: 92%
“…The concurrence between current exposures and sensorineural symptoms in 2001, compared with 1988, may indicate a more temporal or episodic pattern of disease. It is consistent with the observation by Farkkila et al [1988] that, among forest workers, reduced tool vibration had less of an effect on neurological symptoms than vascular symptoms, because of the persistence of biomechanically influenced disorders, such as CTS. Self-reported prior physician diagnosis of CTS had a monotonic association with current exposure, and increased to over 35% of workers in the highest exposure group in the 2001 survey.…”
Section: Effects Of Exposure Reductionsupporting
confidence: 92%
“…In our survey of the literature, there were 21 articles and reports that met the established criteria: 15 crosssectional studies in which 32 occupational or exposure groups had been studied (table 1) (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and six case-referent studies (table 2) (25)(26)(27)(28)(29)(30). All of these studies involved prevalent cases of CTS.…”
Section: Resultsmentioning
confidence: 99%
“…Histopathological studies have demonstrated demyelinating neuropathy with severe destruction and loss of the myelin sheath, and remarkable loss of nerve fibers in finger skin specimens from vibrationexposed subjects 1,2) . Nerve conduction measurements have shown reduced sensory and motor nerve conduction velocities in vibration-exposed hands 3,4) , which are associated with impaired vibration perception thresholds and reduced grip force 5,6) . Vibration perception threshold testing is widely accepted as a useful measure for screening or diagnosing vibrationinduced sensory nerve impairments 7) .…”
Section: Introductionmentioning
confidence: 99%